Meningkatkan Efektivitas Antrian Pada Barbershop Dengan Menggunakan Cutman : Penyedia Jasa Booking Barbershop Berbasis Web - FADLY RAMDHANI; Alif Fadhlan Fadhilah (INTECH, 2024)
Barbershop is now widely recognized in the community. Often people are annoyed by the queues that are full and long waits. Cutman is a web-based application that allows customers to book from home and can choose the time and also choose a haircut that suits the customer at Cutman Barbershop. In this way the customer can access the website, then the customer can make a booking by selecting the time and also the haircut. The Cutman application is designed using Visual Studio code (Vscode), PHP, HTML, Java script, and MySQL. This study uses a Likert scale. With this website, it can help customers in ordering shaving services online.